Changing Sex-Ratios among Immigrant Communities in the U.S. - Adriana Hernández Cata\~neda; Todd A. Sorensen (Institute of Labor Economics (IZA), 2018)
Marriage patterns of immigrants are an important indicator of the degree of immigrant integration into their host countries. Literature on the economics of the household has focused on the role of the sex-ratio as an important determining factor in marriage market outcomes. Therefore, it is important to understand if and how the sex-ratio has changed over time and the mechanisms that may drive that change. In this paper, we explore recent changes in the sex-ratio among immigrants to the United States. First, building upon previous research, we document the nongender neutral nature of declining immigration to the United States. We approach this study from two different dimensions to document some of the forces driving this change in the sex-ratio. The first approach, focusing on changes between birth cohorts, demonstrates that immigration is declining more quickly for men than it is for women, leading to a decrease in the sex-ratio from above 100 and thus bringing about more gender balanced migration. Second, we present results from an analysis of data on recently granted green cards, suggests that the sex-ratio among this population is increasing from below 100, also bringing about more gender-balance among immigrants.
Keywords: F22; J11; J12; 330; demographic change; sex-ratios; immigration